Factors Affecting Security Behavior of Kenyan Students: An Integration of Protection Motivation Theory and Theory of Planned Behavior - Ali Farooq; Joshua Rumo A. Ndiege; Jouni Isoaho (United States, 2022)
The purpose of this study was to identify the factors that affect the security behavior of Kenyan University
Students. Using Protection Motivation Theory (PMT) and Theory and Planned Behavior (TPB) as the theoretical base, data was collected from 125 Kenyan university students through an online survey. Data Analysis was carried out using structural equational modeling (SEM) in SmartPLS 3.2. The analysis showed that among PMT constructs, only self-efficacy played a significant role towards intention to take security measures, whereas, the attitude was the only construct TPB which had a meaningful relation with behavioral intention. Lastly, out of three constructs depicting social influence, only social support had a significant relationship with the behavioral intention. Constructs such as perceived vulnerability, perceived severity, response cost, response efficacy, subjective and descriptive norms did not show a significant relationship with the security intention of the students.
2019 IEEE Africon